Cooperation to promote the adoption of electricity efficient consumption technologies electricity consumption - Parra Valencia, Jorge Andrick; Pineda Ballesteros, Eliécer; Lizcano Dallos, Adriana Rocio (UNIVERSIDAD ANTONIO NARIÑO, 2016)
This paper presents a model based on differential equations which evaluates the effect of changing the delay value of cooperation in a mechanism based on trust, which was implemented to promote the adoption of efficient technologies electricity consumption in a simulation model. The model used system dynamics to study the effects of delays in promoting cooperation to reduce CO2 emissions by adopting efficient technologies of energy consumption. We claim this conclusion is important to develop institutions which promote effective cooperation to solve climate change.